Síntese e caracterização de uma cobaltoftalocianina disubstituída pelo ligante 1,3-bis(4-piridil)propano - Marcondes, Lia Mara Silva (2015)
Due to environmental concerns, currently the search for energy sources that are cleaner and renewable are issues of extreme importance. Based on these principles and work reported in the literature is proposed to obtain a new complex formed by a metal phthalocyanine with potential application in photovoltaic devices. The article also discusses the development of a new sequence of solvents to metal phthalocyanines purification. The survey of a new method of purification was inserted because of the described methods that are generally complex and associated to a certain metal phthalocyanines. The solvents ethanol, methanol, distilled water and acetone were chosen for purification sequence, based on the solubility testing of products and precursors to metal phthalocyanines (M = Cr, Mn, Fe, Co, Ni, Cu e Zn). The characterization of all of these complexes was carried out by electronic and vibrational spectroscopy, thermal analysis and elemental analysis. The data obtained from this characterization suggests the formation of complexes with high purity and absence of solvents in the structures. About the new complex, a axially disubstituted cobalt(II)phthalocyanine (CoPc) by ligand 1,3-bis(4-pyridyl)propane (BPP) named [CoPc (BPP)2] has been described. This complex was characterized by electronic, vibrational and fluorescence spectroscopy, in addition to thermal analysis, nuclear magnetic resonance and elemental analysis. The analyzes suggest the formation of a complex formed by two BPP ligands coordinated to a CoPc. The photophysical properties (absorption coefficient and fluorescence quantum yield), and photochemical (photodegradation quantum yield) were obtained aiming their future use in solar cells. The increase in the value of the absorption coefficient and the fluorescence quantum yield after the axial substitution was observed. Already the photodegradation quantum yield decreased after the axial substitution, but a good photostability has yet been found when compared to systems formed by metal phthalocyanines with other axial ligands reported in the literature. These results encourage further research using this new bisaxial compound in film layers of photovoltaic devices.